Massive Transfusion. Issue Volume 157:Issue (2011)Supplement 3 (1st September 2011) - Doughty, HA; Woolley, T; Thomas, GOR
Abstract : Massive Transfusion is a part of Damage Control Resuscitation. The aim of transfusion therapy is to restore oxygen delivery to poorly perfused tissues and to treat the acute coagulopathy of trauma. The severity and complexity of modern injuries have led to the use of swift, protocol-driven care with the use of 'Shock Packs' and management of metabolic complications. The pro- active treatment of the coagulopathy has been termed Haemostatic Resuscitation. The delivery of this transfusion capability has required an increasingly sophisticated logistic and laboratory response. New operational capabilities have included cold chain solutions; laboratory management information systems; platelet apheresis and ROTEM®. This investment in the massive transfusion capability has delivered rapid resuscitation. It has also enabled clinicians to direct individualised transfusion support following initial resuscitation i.e. goal directed therapy. Future technical solutions should further support the pre- hospital delivery of transfusion while addressing the logistic tail. However, the key to success is the knowledge and skills of frontline staff to deliver safe and appropriate blood transfusion.